The Symbol of Illuminati in Murder Case as Seen in Dan Brown Angels and Demons - Yusuf, Feby Meuthia; Rohana Sihotang, Hendro Hotni (Fakultas Sastra Universitas Ekasakti, 2024)
This research discusses a literary work by Dan Brown, namely a novel entitled Angels and Demons which was first published in 2000. Dan Brown is an American writer who was popular in the 2000s. Angels and Demons is a novel that tells readers about the struggle of a professor in solving an Illuminati symbol puzzle in a murder case that occurred at the Conseil Europeen pour la Recherche Nucleaire and the Vatican.This novel tells the story of a symbology professor, Robert Langdon, who tries to solve the mystery of the Illuminati symbol in a murder case committed by the Illuminati (an ancient underground fraternity group) who tried to destroy the Vatican. Where he got help from Vettra (adopted son of the murdered professor at CERN, Conseil Europeen pour la Recherche Nucleaire) who is also a researcher from the Conseil Europeen pour la Recherche Nucleaire.In analyzing the problems found, the author uses objective theory as a tool to solve problems. Through the use of this theory, the novel Angels and Demons becomes an object for analysis. To support objective theory, structural theory is used in this research. This theory is used to analyze the structures contained in the novel. This research will focus on analyzing the story in the novel. The approach used is a semiotic approach as a way to analyze the signs or symbols in the novel, and to connect the story and symbols in the novel with existing science and reality.After analyzing the novel, three main factors were found in the mystery of the Illuminati symbol. The first factor is the mystery of the emergence of the Illuminati in the case of the murder of a scientist with an Illuminati symbol stamped on his body. The second factor is the mystery of the Illuminati symbols that appeared in the murder case, and the last is about the motive for the theft and murder case that occurred among the Pope candidates who will take part in the Pope's selection at the Vatican.